2023
DOI: 10.3389/fmicb.2023.1180319
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of mycorrhizal helper bacteria of Vaccinium uliginosum and their interaction with mycorrhizal fungi

Abstract: Mycorrhizal helper bacteria (MHB) can promote mycorrhizal fungal colonization and form mycorrhizal symbiosis structures. To investigate the effect of interactions between mycorrhizal beneficial microorganisms on the growth of blueberry, 45 strains of bacteria isolated from the rhizosphere soil of Vaccinium uliginosum were screened for potential MHB strains using the dry-plate confrontation assay and the bacterial extracellular metabolite promotion method. The results showed that the growth rate of mycelium of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…However, global maps of ORC and ERM fungi, as well as ‘mycorrhizal’ Mucoromycota fine‐root endophytes, are still lacking. Furthermore, maps documenting the world‐wide distribution of mycorrhiza‐associated microbes, such as mycorrhiza‐helper bacteria, fungi, and protists, are required to fully understand the breadth of mycorrhizal systems (Frey‐Klett et al ., 2007; Emmett et al ., 2021; Yang et al ., 2023; Zhang et al ., 2023). Identifying the genetic diversity of these mycorrhiza‐associated microorganisms and analyzing their spatiotemporal dynamics is crucial, as emerging studies have suggested their involvement in nutrient uptake facilitation and other services provided by mycorrhizal hyphae (Zhang et al ., 2022; Li et al ., 2023; Wang et al ., 2023a,b).…”
Section: Mapping Mycorrhizal Diversitymentioning
confidence: 99%
“…However, global maps of ORC and ERM fungi, as well as ‘mycorrhizal’ Mucoromycota fine‐root endophytes, are still lacking. Furthermore, maps documenting the world‐wide distribution of mycorrhiza‐associated microbes, such as mycorrhiza‐helper bacteria, fungi, and protists, are required to fully understand the breadth of mycorrhizal systems (Frey‐Klett et al ., 2007; Emmett et al ., 2021; Yang et al ., 2023; Zhang et al ., 2023). Identifying the genetic diversity of these mycorrhiza‐associated microorganisms and analyzing their spatiotemporal dynamics is crucial, as emerging studies have suggested their involvement in nutrient uptake facilitation and other services provided by mycorrhizal hyphae (Zhang et al ., 2022; Li et al ., 2023; Wang et al ., 2023a,b).…”
Section: Mapping Mycorrhizal Diversitymentioning
confidence: 99%
“…These can support mycorrhizal fungi growth, enhance the uptake of nutrients by plants, and also safeguard the plant from diseases [72]. Yang et al [73] sampled 45 kinds of bacterial strains from the rhizosphere soil of Vaccinium uliginosum and selected MHB strains by aiming at dry-plate confrontation and the promotion of extracellular bacterial metabolites. The growth rate of Oidiodendron maius 143, an ericoid mycorrhizal fungal strain, was enhanced by 33.33 and 77.77% for bacterial strain L6 and LM3 exposure, respectively, as revealed by the dry plate confrontation assay.…”
Section: (C) Mycorrhiza-microorganisms Interactionmentioning
confidence: 99%
“…Thus, the growth of L6 and LM3 and O. maius 143 is self-promoting, and the co-inoculation of L6 and LM3 and O. maius 143 can promote the growth of blueberry seedlings and provide theoretical guidance for the exploration of the mechanism of the ericoid mycorrhizal fungi-MHB-blueberry symbiotic relationship. It provided the technical premise for the comprehensive development of biocontrol strain resources and the formulation of biological fertilizer [73].…”
Section: (C) Mycorrhiza-microorganisms Interactionmentioning
confidence: 99%
“…Its significant horticultural and medicinal value [2][3][4][5]. R. dauricum is closely associated with its mycorrhizal microbiota, and this symbiotic relationship plays a crucial role in plant growth, adaptation, and ecosystem functionality [6][7][8]. The symbiotic partnership supports plants through nutritional supply, stress resistance, and disease protection [7,9].…”
Section: Introductionmentioning
confidence: 99%